Naturally elevated arsenic in the Altiplano-Puna, Chile and the link to recent (Mio-Pliocene to Quaternary) volcanic activity, high crustal thicknesses, and geological structures. (January 2021) - Tapia, J.; Schneider, B.; Inostroza, M.; Álvarez-Amado, F.; Luque, J.A.; Aguilera, F.; Parra, S.; Bravo, M.
Abstract: The compilation of water, sediment, rock, and condensed gas data of arsenic (As) in the Altiplano-Puna of Chile reveals a link between its natural enrichment and volcanic activity, high crustal thicknesses, and regional structures. Two zones were studied which encompass the Altiplano-Puna and western lowlands of Chile: the Northern Zone (including Los Pintados, Surire, and Huasco) and Southern Zone (including Pedernales, Grande, and Laguna Verde). A positive correlation was found between average As concentrations in saline and brackish water of salt flats and crustal thicknesses of the two studied zones with heightened values to the east (up to 25 mg∙L −1 of dissolved As in water and a 64 km depth to the Mohorovicic discontinuity). Furthermore, in the studied Altiplano-Puna salt flats, surrounding Mio-Pliocene to Quaternary felsic and intermediate volcanic outcrops are abundant and As is well correlated with other dissolved components (e.g. Li and B). Sediments show extreme As values at punctual locations within the Altiplano-Puna, where the crust is thick, recent volcanic and hydrothermal activity is present, and regional faults are found. Volcanic rocks and condensed gas in the Altiplano-Puna are also enriched with As (up to 221 and 1234 mg∙kg −1 respectively). In this tectonic environment, it is hypothesized that volcanism represents an important source of As and the thick continental crust can provide a large reservoir of As that can be leached by rising thermal fluids. Regional scale fault systems also can allow for preferential upwelling and the heightened concentration of As in fractures. Hydrological processes at the surface transport dissolved As to lower elevation regions through groundwater in aquifers and surface water in perennial rivers, creeks, and gorges, diluting element concentrations where significant evapoconcentration is not present. Graphical abstract: Image 1 Highlights: Naturally enriched arsenic was studied in an active subduction zone. This work integrated arsenic data from water, sediments, rocks, and condensed gas. High arsenic is associated with young felsic-intermediate volcanic outcrops. The thick continental crust is correlated with increased arsenic in the studied media. Anomalous arsenic concentrations are also associated with regional fault zones.